1999
DOI: 10.1046/j.1523-1747.1999.00782.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of IL-10, IL-12, and IFN-γ in the Epidermis of Hairless Mice by UVA (320–400 nm) and UVB (280–320 nm) Radiation

Abstract: We have observed recently that the suppression of contact hypersensitivity (CHS) induced in mice by UVB irradiation may be prevented by suberythemal exposure to UVA radiation. Because the UVB-immunosuppressed state is associated with an upregulation of the Th2-associated cytokines IL-10 and IL-4, and a deficiency in Th1-associated IL-2, IL-12, and IFN-gamma, and because UVA photoimmunoprotection appeared to be IFN-gamma- dependent, we tested the hypothesis that UVA immunoprotection results from an ability to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
2
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 33 publications
6
52
2
2
Order By: Relevance
“…Irradiation with UVA, which we know to protect the mouse from UVB-immunosuppression, significantly reduced UVB-induced FasL expression. This result may indicate that UVA immunoprotection against UVB may result not only from the up-regulation of immunoprotective Th1 cytokines in the epidermis as our previous study suggested, 2 but also from the maintenance of the cutaneous immune balance via the Fas/FasL system. Thus the reduced presence of IFN-γ and the enhanced expression of FasL in the UVB-irradiated epidermis, both indicators of immunosuppression, have been reversed by the immunoprotective UVA irradiation.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Irradiation with UVA, which we know to protect the mouse from UVB-immunosuppression, significantly reduced UVB-induced FasL expression. This result may indicate that UVA immunoprotection against UVB may result not only from the up-regulation of immunoprotective Th1 cytokines in the epidermis as our previous study suggested, 2 but also from the maintenance of the cutaneous immune balance via the Fas/FasL system. Thus the reduced presence of IFN-γ and the enhanced expression of FasL in the UVB-irradiated epidermis, both indicators of immunosuppression, have been reversed by the immunoprotective UVA irradiation.…”
Section: Discussionsupporting
confidence: 52%
“…1 We observed different cytokine modulation in mouse epidermis by the UVA and UVB wavebands: UVA acts as an inducer of Th1-derived cytokines like IL-12 and IFN-γ, while UVB is responsible for induction of Th2-derived cytokines like IL-10, a major cause of immunosuppression. 2 However, the underlying mechanism(s) by which UVA achieved immunoprotection against UVB have remained undefined. Recently, much attention has focused on the apoptosis process during immune responses to UV irradiation, in which the Fas/FasL system has been reported to play a major role.…”
Section: Introductionmentioning
confidence: 99%
“…Digital micrographs were acquired with an Olympus BX40 microscope, and the percentage of total vessel wall area occupied by positive staining was determined by use of ImagePro Plus 4 (Cybernetics). 24 …”
Section: Immunohistochemistrymentioning
confidence: 99%
“…UVA exposure also results in a rapid increase in interferon-g (IFN-g) levels in the skin, the source of which may be resident epidermal T cells (232). Elevated IFN-g mRNA levels are noted in lesions of cutaneous LE (234).…”
Section: Uva Mediated Cytokine Expressionmentioning
confidence: 99%